Observational cohort study protocol: neutrophil function and energetics in adults with pneumonia and sepsis – Pneumonia Metabolism in Ageing (PUMA) - Aaron Scott; Elizabeth Sapey; David R Thickett; Frances S Grudzinska; Aduragbemi A Faniyi (BMJ Open Respiratory Research)
Introduction Community-acquired pneumonia has high mortality and is associated with significant healthcare costs. In older adults with community-acquired pneumonia neutrophil dysfunction has been identified and is associated with poor outcomes for patients. Immunometabolism is a rapidly developing field which links immune cell function to metabolism. This study aims to explore neutrophil metabolism in community-acquired pneumonia.Methods and analysis Pneumonia Metabolism in Ageing study is a prospective observational study recruiting older adults hospitalised with community-acquired pneumonia to examine neutrophil function and metabolic status. Controls will be older adults with no acute illness. The primary endpoint is neutrophil chemotaxis.Ethics and dissemination The study has ethical approval from the Research Ethics Committee Wales, reference 19/WA/0299. This study involves participants who may lack the capacity to consent to research involvement, in this situation, personal or professional assent will be sought. The results from this study will be submitted for publication in peer-reviewed journals and disseminated at local and international conferences.